Козацькі пам'ятки Присамар'я за археологічними дослідженнями. (Zaporizhzhia Historical Review, 2021)
The article is dedicated to the archeological research of Cossack memorials in Prysamarye (Samara region). The conclusion about necessary of using archeological data in Cossack studies has been proved.